Promoting Pre-service Teachers’ Domain-general Metacognition - Briška, Ilze; Siliņa-Jasjukeviča, Gunta (Acta Paedagogica Vilnensia, 2022)
The current study explores the possibilities of promoting the prospective teacher’s domain-general metacognition in the university study process. The aim of the study is to investigate which content of reflection is more relevant for effective enhancing teacher education students’ domain-general metacognition. To reach the aim, the structure of metacognition is analysed; metacognition (MC) components are interpreted from the perspective of transformative learning to define the indices for the domain-general metacognition; a set of open-ended sentences is constructed for reflection which includes all components of MC; and the significance of different sentences for providing the students’ domain-general metacognition is proved in a mixed-methods study.